"Received as a woman": rethinking the concubinage of Aurembiaix of Urgell. Issue 1 (2nd January 2016) - Shadis, Miriam
Abstract : Medieval Iberians practiced a form of concubinage known as barraganía – a potentially time-limited, contractual arrangement between men and women who could not or would not marry. The agreement between Jaume I, ruler of the Crown of Aragon, and Aurembiaix, the Countess of Urgell, made at Agramunt in October 1228, has been cited as an example of a concubinage contract. This article examines their agreement as an example of a feudal convenientia, produced in the context of earlier convenientiae between Jaume's father and grandfather and Aurembiaix's parents, Count Ermengol VIII and Countess Elvira of Urgell, as well as convenientiae between Ermengol and Elvira themselves. I argue that the introduction of women – and gendered language surrounding them – into feudal protocols confuses historians who see sex when language is gendered, and have therefore understood Aurembiaix's agreement as primarily one of concubinage. Instead, I suggest it should be understood as a typical convenientia, one that solved a specific problem for the countess, who was desperate for heirs, and included the possibility that she might have them with King Jaume.